2022
DOI: 10.1038/s41598-022-21873-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevelance of depression and anxiety with their effect on quality of life in chronic kidney disease patients

Abstract: Chronic kidney disease is one of the most common chronic diseases globally. Many studies have shown it is strongly associated with increased social and psychological problems such as depression and anxiety which are considered as common psychiatric disorders that occur in patients with chronic kidney disease. We investigated the prevalence of depression, anxiety and perception of quality of life in a sample of chronic kidney disease patients at the Jordan University Hospital. We aimed to see any association of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 33 publications
1
11
0
1
Order By: Relevance
“…In a study conducted by Sameeha et al, the researchers investigated predialysis CKD patients and found the prevalence to be about 58%. 15 It’s well established that depression is the most common psychiatric illness found among hemodialysis patients, in particular with a prevalence that varies between 20% at the lowest to 88.8% at the highest, 2 , 7 , 16–28 while most of the studies have shown the depression prevalence to be around 50% or more. 29 Anxiety is also a common psychiatric disorder among Hemodialysis patients, with a prevalence ranging from 23.6% at the lowest to 92.5% at the highest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted by Sameeha et al, the researchers investigated predialysis CKD patients and found the prevalence to be about 58%. 15 It’s well established that depression is the most common psychiatric illness found among hemodialysis patients, in particular with a prevalence that varies between 20% at the lowest to 88.8% at the highest, 2 , 7 , 16–28 while most of the studies have shown the depression prevalence to be around 50% or more. 29 Anxiety is also a common psychiatric disorder among Hemodialysis patients, with a prevalence ranging from 23.6% at the lowest to 92.5% at the highest.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 19 , 42–46 Sameeha et al conducted a study in Jordan and found that married CKD patients had a significantly lower prevalence of depression. 15 An interesting study of 3865 participants from 2005–2014 investigated the effect of marital status on depression among CKD patients and found a significant relationship between marital status and mortality among CKD patients. 44 However, some studies have not found any association between marital status with anxiety, depression, or QOL.…”
Section: Discussionmentioning
confidence: 99%
“…17 Hal ini disebabkan beban penyakit, pengobatan seumur hidup, modifikasi diet, dan mahalnya biaya pengobatan, merupakan faktor yang berkontribusi terhadap perubahan status psikologis pasien. 18 Faktor lain yang dapat menyebabkan kecemasan pada Tn. D, yaitu terkait proses hemodialisis yang belum lama dijalani.…”
Section: Metode Penelitianunclassified
“…Most of the children depend on dialysis or a kidney transplant for their survival which is not simply accessible in developing and underdeveloped nations. Other major issues with CKD are the prevalence of other serious health conditions like cardiovascular diseases, depression, anxiety, and diabetes (Alshelleh et al, 2022; Jankowski et al, 2021). In a recent study, the risk associated with CKD and outcomes after coronary artery bypass surgery was established (Nowrouzi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%